Uciążliwość i psychologiczne koszty pracy. Negatywne aspekty funkcjonowania w roli właściciela firmy - Biegańska, Katarzyna (Acta Universitatis Lodziensis. Folia Psychologica, 2008)
In the field of work psychology there are posed questions and solved problems which concern individual effectiveness and satisfaction in one's occupational activity. Job is many times related with onerousness, the size of which is modified by personal and situational determinants. The current article contains presentation of theoretical and empirical analyses regarding job onerousness characteristic for the situation of managing one's own enterprise. Two aspects of that onerousness have been distinguished: perceived onerousness (job onerousness perception) and onerousness experienced as psychological costs (psychological costs of work). Researches have been made to examine whether these aspects are modified by some other determinants (both personal and situational determinants have been included). The performed analyses have proved that perceived onerousness depends on temporary engagement in job and financial gratification, and psychological costs of work are determined by neuroticism mainly.